Aksesibilitas, Atraksi dan Fasilitas Pada Daya Tarik Wisata Pacu Jawi, Tanah Datar, Sumatera Barat. - Harahap, Ulfah Azzahra; Cipta Endyana; Alexander M.A.Khan (Yayasan Literasi Sains Indonesia, 2022)
One of the areas in Indonesia that has many cultural elements is Tanah Datar Regency in West Sumatra. Tanah Datar has a variety of cultural attractions, Basa Pagaruyung Palace which is pagaruyung kingdom for example, there is also a Kerbai or Sapi Racing Cultural Tradition commonly called Pacu Jawi. Minangkabau tradition that uses cows or buffaloes in the pacu Bersama with the intention of being grateful for sustenance and expecting blessings. This attraction is done in muddy land or large rice fields and is done during the harvest season. Tanah Datar Regency has a variety of tourist attractions, especially the iconic one in Tanah Datar Regency is Pacu Jawi, where this attraction is very popular with many circles and tourists. Especially from the photography side who judged that